Politik Hukum Kekuasaan Kehakiman di Indonesia - Nuraini Nuraini; Mhd Ansori (Wajah Hukum, 2022)
Judicial power is a branch of power in every country, whether in a democratic state, a state towards a democracy, or an undemocratic state. This happened on the influence of the doctrine of separation of powers which wanted the branches of power to be divided over the legislature, executive, and judiciary. Judicial power in Indonesia at the beginning of independence was intended as a separate branch of power from political institutions, the power of an independent judiciary must still be upheld both as a principle in the state based on law and to allow judicial power to ensure that government is not carried out arbitrarily. The development of judicial power is inseparable from the legal politics of judicial power itself. Because legal politics is subtantively about the friction between politics and law, to examine legal politics is to discuss policies related to the state system. The purpose of the writing is to find out and analyze the political dynamics of judicial power in Indonesia. This type of writing is normative juridical, meaning that this article focuses on the study of the implementation of all positive legal norms and rules. In this research, the approach is conceptual, legal and historical approach.